2021
DOI: 10.5539/ies.v14n9p108
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Perceptions of the Effectiveness of Microsoft Teams for Remote Learning

Abstract: This paper draws on social constructivism and the domestication model and investigates pre-service teachers’ perceptions of the usefulness of Microsoft Teams for remote learning. This research is part of a descriptive cross-sectional study. It is neither causal nor relational. The participants comprised of 215 undergraduate pre-service teachers from an all-female teacher training college in Kuwait and were surveyed during year 1 of their three-year academic programme. Descriptive statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Moreover, the context of the research was conducted at a university in Kuwait, investigating the perception of pre-service teachers on the usefulness of Microsoft Teams during virtual learning. Data were taken from questionnaires, the results showed that Microsoft Teams is a videoconferencing learning platform that is capable of facilitating interactive learning activities and providing immediate feedback [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the context of the research was conducted at a university in Kuwait, investigating the perception of pre-service teachers on the usefulness of Microsoft Teams during virtual learning. Data were taken from questionnaires, the results showed that Microsoft Teams is a videoconferencing learning platform that is capable of facilitating interactive learning activities and providing immediate feedback [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They reported they had not used certain capabilities before the beginning of the experiment, the Chat Rooms, for example. Although this study result is mainly in line with Almodaires et al (2021), the only difference was that Almodaires et al (2021) comprised only female participants.…”
Section: Discussionmentioning
confidence: 48%
“…was novel and encouraging for the students to use in learning because it facilitated interaction and access to educational content. Almodaires et al (2021) had female student teachers at a Kuwaiti female teacher-training college. The study surveyed the EFL students in one of the three years at college studying the English course.…”
Section: Effectiveness In Learners' and Teachers' Perceptionsmentioning
confidence: 99%
“…Literature searches failed to identify similar online showcasing and judging platforms as presented in this report. The use of Edublogs, Teams, and Office applications in their more traditional roles have been well described [ 17 , 18 , 19 ]. However, an application to accomplish an online showcase and judging platforms for research has not been previously described.…”
Section: Discussionmentioning
confidence: 99%